Assessment of two-stream approximations in a climate model. (March 2019) - Yang, Quan; Zhang, Feng; Zhang, Hua; Wang, Zhili; Li, Jiangnan; Wu, Kun; Shi, Yining; Peng, Yiran
Highlights: Two-stream DOM produces more accurate radiative flux under clear-sky conditions. The Eddington approximation can enhance the boundary layer cloud. Eddington approximation is impressively far more accurate under all-sky conditions. Abstract: The accuracies of the two-stream discrete-ordinate-method (DOM) and Eddington approximation schemes are systematically compared using the BCC_RAD radiative transfer scheme used in a general circulation model (GCM). It is found that the two-stream DOM produces more accurate results for the upward radiative flux, downward radiative flux and heating rate under clear-sky conditions in an offline radiation model, whereas the Eddington approximation is more accurate under all-sky conditions. An experiment using satellite data as the approximation of cloud properties confirms the superiority of the Eddington approximation under cloudy-sky conditions. Experiments using the GCM of the Beijing Climate Center (BCC_AGCM2.0.1) show that, compared to the two-stream DOM, the Eddington approximation can enhance the fraction of low cloud, and this increased cloud fraction can affect the differences in radiative fluxes between these schemes. This study suggests that the more suitable approach in GCMs is to use the Eddington approximation.